2021
DOI: 10.1186/s12936-021-03846-4
|View full text |Cite
|
Sign up to set email alerts
|

Residual malaria in Jazan region, southwestern Saudi Arabia: the situation, challenges and climatic drivers of autochthonous malaria

Abstract: Background Saudi Arabia and Yemen are the only two countries in the Arabian Peninsula that are yet to achieve malaria elimination. Over the past two decades, the malaria control programme in Saudi Arabia has successfully reduced the annual number of malaria cases, with the lowest incidence rate across the country reported in 2014. This study aims to investigate the distribution of residual malaria in Jazan region and to identify potential climatic drivers of autochthonous malaria cases in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 45 publications
11
39
0
Order By: Relevance
“…The results of the present study are applicable to reallife scenarios because Jazan is among the tropical cities with average temperature 30.7 ± 2.28 °C within the range of 23.0-35.1 °C (Al-Mekhlafi et al 2021). Hence, the results of the present study confirmed the optimal rearing for C. albiceps at 30 °C and in line with that discussed in previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study are applicable to reallife scenarios because Jazan is among the tropical cities with average temperature 30.7 ± 2.28 °C within the range of 23.0-35.1 °C (Al-Mekhlafi et al 2021). Hence, the results of the present study confirmed the optimal rearing for C. albiceps at 30 °C and in line with that discussed in previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…In Saudi Arabia, a national malaria control programme was established in 1948 and since then, substantial progress has been made in reducing the presence of malaria in the country 18 . Saudi Arabia is now in the elimination phase, and malaria transmission is restricted to specific foci in the southwestern parts of the country, particularly in the regions of Jazan and Aseer 19 , 20 . However, while the number of annual malaria cases decreased steadily between 2000 and 2014, an increasing trend has been observed since 2015, with 3658 cases reported in 2020, and 82.6% of those cases were in Jazan region 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Aseer. The transmission level peaks between December and March; however, malaria cases are reported throughout the year 20 . Different Anopheles species have been identi ed as vectors for malaria in Jazan region, including An.…”
Section: Study Areamentioning
confidence: 99%
“…In Saudi Arabia, a national malaria control programme was established in 1948 and since then, substantial progress has been made in reducing the presence of malaria in the country 18 . Saudi Arabia is now in the elimination phase, and malaria transmission is restricted to speci c foci in the southwestern parts of the country, particularly in the regions of Jazan and Aseer 19,20 . However, while the number of annual malaria cases decreased steadily between 2000 and 2014, an increasing trend has been observed since 2015, with 3,658 cases reported in 2020, and 82.6% of those cases were in Jazan region 20,21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation